Jurnal Penyuluhan: Pemanfaatan Cyber Extension melalui Telepon Genggam oleh Petani Anggrek di Taman Anggrek Ragunan, Jakarta Selatan - Aira Putri Eri Dasli, Pudji Muljono, Djoko Susanto (PPs ILMU PENYULUHAN PEMBANGUNAN IPB, 2015)
Cyber extension is one of the modern technology which can be utilized by the farmers, extension workers, and Business actors to obtain informations and develop agricultural business.